The Influence of Verbal Reinforcement (Praise) on the Motivation to Learn Pancasila Education of Grade VII Students at SMP Negeri 1 Kampung Rakyat in the 2024-2025 Academic Year - Manurung, Evi Prbrianti Br; Junita, Junita; Anjar, Agus (Jurnal Riset Ilmu Pendidikan, 2025)
This study aims to analyze the effect of verbal reinforcement in the form of praise on students' learning motivation in the Pancasila Education subject in class VII of SMP Negeri 1 Kampung Rakyat in the 2024-2025 Academic Year. The approach used is quantitative with a quasi-experimental method. Data collection techniques are carried out through observation, questionnaires, and documentation. The results of the study indicate that verbal reinforcement in the form of praise has a significant effect on increasing students' learning motivation, the results of a simple linear regression equation are obtained as follows: Y = 43.345 + 0.408X1. Based on these calculations, it can be seen that the linear regression coefficient value of the Verbal Reinforcement (Praise) variable (X) is 0.408 with a positive sign at sig 0.000 which is smaller than 0.05, namely 0.000 <0.05. So, it can be interpreted that Verbal Reinforcement (Praise) (X) has a positive effect on the Pancasila Education Learning Motivation of Class VII Students of SMP Negeri 1 Kampung Rakyat (Y). This shows that with every good Verbal Reinforcement (Praise) (X), there will be an increase in the Motivation to Learn Pancasila Education of Class VII Students of SMP Negeri 1 Kampung Rakyat 0.408. This finding indicates that the use of verbal reinforcement such as praise can be an effective strategy for teachers in increasing student learning motivation, especially in the subject of Pancasila Education. Therefore, verbal reinforcement is recommended as part of teaching practices to create a positive learning environment and support student development holistically